COVID-19 vaccine uptake and associated factors among high school students in Lemi Kura Sub-City, Addis Ababa, 2022 - Busa, Etana; Beksisa, Jemal; Reda, Zinabu; Debela, Sisay Abebe (Frontiers in Public Health, 2025)
BackgroundCoronavirus disease 2019 (COVID-19) remains a major global health challenge, mostly affecting developing countries such as Ethiopia, which is facing low COVID-19 vaccination acceptance. This study aimed to assess the uptake of the COVID-19 vaccine and its associated factors among high school students in Lemi Kura Sub-City, Addis Ababa.MethodsAn institution-based cross-sectional study was conducted at public high schools. Self-administered questionnaires were used to collect data from randomly selected high school students. We used Epi Info and SPSS for data entry and analysis. Descriptive and multivariable logistic regression analyses were performed to identify factors associated with COVID-19 vaccination.ResultsOf the 802 participants (95% response rate), 46.2% were vaccinated. A total of 445 students (55.5%) had a positive attitude toward the COVID-19 vaccine, and 319 students (39.8%) had good knowledge about it. In addition, 625 students (78%) had undergone COVID-19 testing, and 286 students (35.7%) reported a history of infection. Factors significantly associated with vaccine uptake were good knowledge (AOR = 2.1, 95%CI: 1.4–3.1), positive attitude (AOR = 14.4, 95%CI: 9.5–22), prior testing (AOR = 2.1, 95%CI: 1.2–3.7), and absence of exposure to negative information (AOR = 2.26, 95%CI: 1.3–3.9).ConclusionThe overall COVID-19 vaccine uptake was low. Knowledge, attitude, prior COVID-19 testing, and exposure to misinformation significantly influenced vaccine uptake among high school students. Improving awareness among the target population is essential to enhancing vaccination rates.